Establishing Civilian Control over the Armed Forces - Broto Wardoyo (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2016)
Using simple regression, this paper examines the explanans to the degree of civilian control over the armed forces. This paper takes into consideration four of the most considered independent variables to explain the degree of civilian control over the armed forces, i.e. internal threat, economic condition, civil liberties, and military access to resources. It suggests that the degree of internal threat is negatively correlated with the degree of civilian control over the armed forces while economic condition, civil liberties, and defense spending, or access to resources, enhance the degree of civilian control over the armed forces. In addition, it also suggests that civil liberties have the highest influence to the degree of civilian control over the armed forces, controlling the other independent variables. Since civil liberties are closely related to degree of democracy, it basically confirms previous research that suggest the degree of civilian control is closely and positively correlated with the maturity of democracy.